PERLAKUAN AKUNTANSI ATAS PENYUSUTAN ASET TETAP DALAM PENYAJIANNYA PADA LAPORAN KEUANGAN (Studi Kasus pada PT. Karya Lestari di Sidoarjo) - Heri Toni Hendro Pranoto; Abdurrahman Saleh Bin Agil (Fakultas Ekonomi Universitas 45 Surabaya, 2020)
Fixed assets are long-term assets or assets that are relatively permanent. They are tangible assets because they are physically visible. The purpose of this study is to determine which method of depreciation of fixed assets is more appropriate for PT. Karya Jaya Lestari Sidoarjo. The method used in this research is descriptive qualitative method. The results of this study indicate that the companies concerned have not implemented a depreciation method in accordance with the type of business of the company concerned. Therefore, this study provides suggestions and reconstructs the depreciation of fixed assets in accordance with the type of business of the company concerned, which can provide a fair presentation of the depreciation method for fixed assets in the financial statements.